Stress-strain and limiting state of spoked flywheels formed from composite materials. Report 1. Computational relationships - Leshchenko, V.M.; Kosov, B.D.; Kozlov, I.A. (Проблемы прочности, 1985)
The purpose of the present study is to obtain a rather simple solution for this problem which is convenient for practical engineering computations, and to evaluate its discrepancy with the accurate solution, and also its correspondence with experimental data on the limiting bearing capacity for two flywheel models of various composite materials.